Analisis Faktor-Faktor Kecurangan Laporan Keuangan melalui Fraud Hexagon Theory pada Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2016-2019 - Khalyacara Febrianto; Dhini Suryandari (Permana : Jurnal Perpajakan, Manajemen, dan Akuntansi, 2022)
The purpose of this study is to examine the factors that influence financial statement fraud through the fraud hexagon theory. The population in this study are all mining sector companies listed on the Indonesia Stock Exchange which are included in the company sample criteria in the 2016 to 2019 period, namely as many as 32 companies. Sampling was carried out by purposive sampling technique and 100 units of analysis were selected after the data outlier technique was carried out. The measurement used to calculate financial statement fraud is earnings management. In addition, the software used is SPSS IBM 24. The results show that the financial target and the nature of the industry have a significant positive effect on financial statement fraud, while the external pressure, change of directors, collusion, and change of auditors have no significant effect on fraudulent financial statements. Meanwhile, the CEO duality variable has a negative but not significant effect on financial statement fraud. The limitation of this research is that the collusion proxy is measured using a joint project with the government, so suggestions for further research are expected to use other proxies such as political connections or state-owned enterprises.